IMPLEMENTASI TEKNIK LOCAL SEARCH ENGINE OPTIMATION (SEO) MENGGUNAKAN GOOGLE MY BUSSINESS (STUDI KASUS DI TB. JAYA SUKSES) - Muhammad Lutfi Mahasinul Akhlak (TRANSFORMASI, 2021)
The development of connectivity and better use of data through the Internet has turned the world into a global village. The innovation of digital service products makes consumers easy to reach through digital marketing. To market a product on the Internet, in addition to creating a creative and content-rich website, another very important thing is to get the website to be at the top of the Search Engine Result Pages (SERPS) of the Search Engines or search engines. SEO tools can be used to increase traffic or traffic to websites so that they can increase the income of an online business. One of the tools from Google that can be used to manage the appearance of a business on Google search pages and Google Maps is Google My Business. This research focuses on implementing Local Search Engine Optimization (SEO) using Google my business and also analyzing the influence of keywords. which positively affects digital marketing. The conclusion of this research is that Google My Business is very effective for local SEO optimization so it is very efficient and economical for funneling or sales funnels in digital marketing. Keywords: Google My Business, Local SEO, Digital Marketing